Nonclinical Development of Biologics: Integrating Safety, Pharmacokinetics, and Pharmacodynamics to Create Smarter and More Flexible Nonclinical Safety Programs Optimizing Animal Use. (May 2021) - Hey, Adam; Baumann, Andreas; Kronenberg, Sven; Blaich, Guenter; Mohl, Silke; Fagg, Rajni; Ulrich, Peter; Rattel, Benno; Richter, Wolfgang F.; Kiessling, Andrea; Weir, Lucinda
Safety assessment of biological drugs has its challenges due to the multiple new different modalities, for example, antibody-drug conjugates, bispecifics, nanobodies, fusion proteins and advanced therapy medicinal products (ATMPs), their different pharmacokinetic and pharmacodynamic properties, and their ability to trigger immunogenicity and toxicity. In the public and in the pharmaceutical industry, there is a strong and general desire to reduce the number of animals used in research and development of drugs and in particular reducing the use of nonhuman primates. Important discussions and activities are ongoing investigating the smarter designs of early research and dose range finding studies, reuse of animals, and replacing animal experiments with in vitro studies. Other important challenges include absence of a relevant species and design of studies and developing genetically modified animals for special investigative toxicology studies. Then, the learnings and challenges from the development of the first ATMPs are available providing valuable insights in the development path for these new potentially transformative treatments. Finally, development of strategies for assessment of immunogenicity and prediction of translation of immunogenicity and associated findings to the clinic. On this, the eighth meeting for the European BioSafe members, these challenges served as the basis for the presentations and discussions during the meeting. This article serves as the workshop report reviewing the presentations and discussions at the meeting.